Efficacy of foliar fungicides on controlling early blight disease of Eggplant, under laboratory and greenhouse conditions - Abdulnabi A. A. Matrood; Abdelhak Rhouma (Novel Research in Microbiology Journal)
The eggplant production has gone through increasing difficulties due to relatively low yields in the last few years in Iraq. Alternaria solani, the causal agent of eggplant early blight; attacks hybrid and local varieties either in open field or in the greenhouse, causing a serious damage that led to decrease in crop yield. The strategies employed to manage this disease by Iraqi farmers were the synthetic fungicides application. In this study, several assays were conducted such as poisoned food technique (in vitro assay) and greenhouse experiment (in vivo assay); to evaluate the inhibitory efficacy of 3 three synthetic fungicides including; Topas® 100 (penconazole), Tilt 250 (propiconazole) and Leimay® (amisulbrom) on A. solani mycelial growth and disease intensity. In laboratory assays, Topas® 100 and Tilt 250 exhibited high inhibitory activities against A. solani as an airborne pathogen; recording mycelial inhibition rate above 94 % at a concentration of 1000 mg\ l. Furthermore, these two fungicides when applied preventively in greenhouse assays reduced significantly the disease severity index (DSI) by 18.83 % and 26.16 %, respectively. Current results revealed that Topas® 100 and Tilt 250 caused the highest antifungal potential manifested through reduction rate of fresh weight (9.62 and 8.58 g, respectively), and dry weight (4.61 and 4.60 g, respectively). Moreover, both fungicides recorded the highest peroxidase activities of 4.128 units/g/ml/min. and 3.038 units/g/ml/min., respectively. Current findings can be used to assist the eggplant growers to improve the control of early blight disease, and increase the marketable yields of this crop.